Evaluation of the Distribution Pipe Network System in Adi Mas Giri Housing, Banyuwangi, using E-PANET 2.0 and Quantum GIS - Reza, M. Ivan Adi; Purnomo, Dimas Aji; Sujatmiko, Heri (Jurnal Teknik Sipil, 2025)
Clean water supply is one of the crucial aspects that must be considered in every region. PDAM is responsible for meeting clean water needs by considering quality, quantity, and continuity. A distribution network that does not meet the standards will hinder fulfilling the community's clean water needs. Tools such as E-PANET are needed to analyze and optimize the water distribution system, which can be used in the design, hydraulic model calibration, residual chlorine analysis, and customer evaluation. This research was conducted in Adi Mas Giri Banyuwangi Housing, Banyuwangi Regency, using a quantitative analysis using E-PANET 2.0 and GIS software. The results showed that the clean water demand in Adimas Giri Banyuwangi Housing was 0,2784 liters/second. Meanwhile, the analysis results using E-PANET 2.0 show that the clean water distribution network in the area has not functioned optimally. Therefore, improvement efforts are needed, such as replacing large-diameter pipes that do not flow with smaller ones, adjusting the pressure in the system, and identifying potential bottlenecks in the network. With this optimization, clean water distribution in Adi Mas Giri Housing is expected to be more efficient and equitable.